PD-L1 and Notch as novel biomarkers in pancreatic sarcomatoid carcinoma: a pilot study. (2nd November 2021) - Silvestris, Nicola; Argentiero, Antonella; Brunetti, Oronzo; Sonnessa, Margherita; Colonna, Fulvia; Delcuratolo, Sabina; Luchini, Claudio; Scarpa, Aldo; Lonardi, Sara; Nappo, Floriana; Fassan, Matteo; Solimando, Antonio Giovanni; et al.
ABSTRACT: Background: The improved immunological understanding revealed the tumor microenvironment as an appealing driver to restore the immune response against cancer cells resulting in a paradigm shift in the oncology field. However, the complexity of the tumor milieu suggests the role of several pathways linking in immunomodulation mechanisms. Pancreatic cancer represents a model of the intricate relationship between malignant cells and their surrounding neighborhood. Research Design and Methods: In this study, we analyzed, retrospectively, six cases of rare pancreatic sarcomatoid carcinoma (PSC) and evaluated the expression of PD-L1 and Notch, aiming to explore new attributes in immunophenotype. Results: PD-L1 CPS ≥ 1was common in PSCs (83%) with half samples expressing PD-L1 CPS ≥ 50. Notch1 and Notch3 demonstrated a high range of expression. A direct significant correlation between PD-L1 and Notch3 overexpression (r = 0.7; p = 0.036) has been observed. Immunofluorescence studies revealed a co-localization of Notch3 and PD-L1 when both proteins were over-expressed within cytoplasmic or membranous compartments of the same cells. Conclusions: Our data identify a unique biological characterization of this rare pancreatic histotype. These findings provide a rationale for future studies evaluating the potential crosstalk between PD-L1/PD-1 axis and Notch pathways and prompting the development of novel therapeutics strategy.